Verdientes Wohlergehen Philosophische Gerechtigkeit und empirische Moralforschung - Heepe, Moritz (Mohr Siebeck, 2019)
Just deserts or deserved payoff? What does it mean to earn punishment or reward? How should the important goods in life be fairly divided? Moritz Heepe responds to these questions by developing a basically Aristotelian principle of justice that has been neglected in modern discourse, but is firmly rooted in the human sense of justice adequately described by moral psychology.
PublicationDate: 20190124
Keywords: Strafrechtliche Verantwortlichkeit -- Verdienst -- user generated content -- Öffentlichkeitsgrundsatz -- Vergeltung -- Evangelische Akademie -- Ministry -- Strafgerechtigkeit -- Reziprozität -- Konsequenzialismus -- Ethik -- Rechtsphilosophie